Pendidikan Karakter dalam Mewujudkan Pendidikan yang Berkualitas Sesuai dengan SDGs di SMAS Syekh-Yusuf Kota Tangerang - Faiz Fikri Al Fahmi; Ahmad Ahmad; P Fitria Firdiyani; Sri Jaya Lesmana (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Character education is a fundamental aspect in creating quality and integrity human resources. In line with the 4th SDGs on quality education, character education is expected to form students who are not only academically superior but also have high morality. The PKM activity, which was held on Thursday, January 9, 2025, aimed to increase students' understanding of the importance of character education based on religious values in daily life through counseling methods at SMAS Syekh-Yusuf, Tangerang City. Counseling was carried out with an interactive approach involving group discussions, case studies, and role simulations so that participants could more easily understand and internalize character values such as honesty, responsibility, discipline, and empathy. To measure the effectiveness of the program, pretest and posttest were given to determine the improvement of students' understanding before and after counseling. The results of the evaluation showed a significant increase in students' understanding of the concept of character education and its implementation in daily life, which was 66%. With these achievements, it is hoped that students will be able to apply character values consistently in the school and community environment and become a generation with integrity, in accordance with the goals of quality education in the SDGs.